Adenocarcinoma cells in effusion cytology as a diagnostic pitfall with potential impact on clinical management: A case report with brief review of immunomarkers. Issue 3 (16th November 2012) - Chowdhuri, Sinchita Roy; Fetsch, Patricia; Squires, Jennifer; Kohn, Elise; Filie, Armando C.
<x xml:space="preserve">Abstract</x> Distinguishing metastatic carcinoma cells from reactive mesothelial cells in effusion samples is often challenging based on morphology alone. Metastatic carcinoma cells in fluid samples may mimic reactive mesothelial cells due to overlapping cytological features. We report a case of a pleural effusion in a 51‐year‐old female patient with a medical history significant for bilateral ovarian tumors and peritoneal implants diagnosed as serous tumor of borderline malignant potential. The effusion was composed almost entirely of adenocarcinoma cells that morphologically mimicked reactive mesothelial cells. The diagnosis of metastatic adenocarcinoma was made after a wide immunostaining panel of antibodies. Recognizing metastatic adenocarcinoma cells in effusion samples can be challenging and an accurate diagnosis may have significant impact on clinical management as demonstrated by this case. Diagn. Cytopathol. 2012;42:253–258. © 2012 Wiley Periodicals, Inc.